Volume Tables for Acacia auriculiformis - Mittal, M. C.; Singh, Jai; Rai, M. P.; Rawat, J. K. (Indian Forester, 1991)
In this paper general and Volume Tables for Acacia auriculiformis have been prepared and developed using regression methods on volume data collected from sample plots of Orissa.